If f(x)=x^2-3 and g(x)=5x-2, evaluate f(-1)-g(2)?

### 2 Answers | Add Yours

`f(x)=x^2-3` `g(x)=5x-2`

`f(-1)=(-1)^2-3=1-3=-2` `g(2)=5 xx 2-2=10-2=8`

So `f(-1) - g(2)= -2-8=-10`

To evaluate expressions like `f(-1)-g(2)` , we need to remember that a function evaluation is just a number, and that two numbers may be subtracted like in that expression. This means that each function needs to be evaluated separately, then subtracted.

`f(-1)-g(2)` sub -1 in f(x) and 2 in g(x)

`=((-1)^2-3)-(5(2)-2)` now evaluate, being careful with order of operations

`=(1-3)-(10-2)` continue to work from the inside out

`=(-2)-8`

`=-10`

**The expression evaluates to -10.**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes